Ethics in translation practice - May Bennet, Phillipa (Verba hispanica, 2021)
The interest in and understanding of ethics among translation scholars has changed dramatically since the publication of Andrew Chesterman’s proposal for a Hieronymic Oath (Chesterman, 2001). Early definitions of ethics based on equivalence (Newmark, 1991), faithfulness, loyalty (Nord, 1997) and trust have been put aside in favour of more recent notions of translator ethics grounded in accountability (Baker & Maier, 2011) and social responsibility (Drugan & Tipton, 2017). Practising translators who abide by codes of ethics/conduct are bound by principles of honesty, integrity, linguistic competence, confidentiality, and trust. This paper begins by presenting a brief literature review of the main developments in translation ethics from the early linguists to contemporary interpretations. There then follows an analysis and comparison of several professional codes of conduct from the main international associations of translators and interpreters with the benchmark, the Associa-tion of Translation and Interpreting Professionals (APTRAD). It is one of the more recent translator associations and has a code of conduct adopted in the last six years. The objective of this paper is to determine which theoretical definitions of ethics are reflected in the codes of conduct and to discuss their usefulness for translators in their daily practice. The paper ends with recommendations for changes to codes of conduct to make them more relevant to practising translators.
Keywords: codes of conduct; codes of ethics; etični kodeksi; kodeksi ravnanja; prevajalska združenja; prevajanje; tolmačenje; translation associations; translator ethics